Linear polymer comprising dual functionalities with hierarchical pores for lithium ion batteries - Aher, Jagadish D.; Palani, Sathishkumar; Krishnamoorthy, Kothandam (Chemelectrochem, 2023)
Organic materials with carbonyl, azo, nitrile and imine moieties are widely used in lithium batteries. The solubility of these materials in battery electrolytes is an issue. Aggregation of the organic molecules can suppress the solubility, but the accessibility of lithium-ion is hindered. Therefore, insoluble porous organic materials are desired. Herein, we synthesized a linear polymer with carbonyl and azo functionalities. Due to the presence of easily isomerizable azo moiety, a porous polymer was obtained. The polymer showed nano and micropores. The battery with the porous polymer showed an impressive specific capacity of 400 mA h/g at 0.2 A/g. If the battery is pre-conditioned, the specific capacity increased to 615 mA h/g at the same current density. The post-mortem analysis of the battery confirmed that the polymer didn't dissolve in the battery electrolyte. The control material is a small molecule with carbonyl and azo moieties that showed a poor specific capacity of 40 mA h/g indicating the necessity to have a hierarchically porous dual-functional polymer. Polymers for batteries: A linear polymer with micro and Nano pores with azo and carbonyl functionalities renders increased accessibility to Li ions after preconditioning. During charge-discharge experiment Azo-Carb-PDI electrode had impressive discharge capacity of 469 mA h/g after 500 cycle which is almost 15 times higher than the monomer (Azo-PDI-Azo, 30 mA h/g after 100 cycle).image
Keywords: azo polymer; carbonyl; Li-ion battery; porous polymer; Rylene-imide